Fiscal Monitor, April 2020 : Policies to Support People During the COVID-19 Pandemic. (Fiscal Monitor; Fiscal Monitor, 2020)
Chapter 1 argues that fiscal policies are at the forefront of responding to the COVID-19 pandemic. Fiscal measures can save lives, protect the most-affected people and firms from the economic impact of the pandemic, and prevent the health crisis from turning into a deep long-lasting slump. A key priority is to fully accommodate spending on health and emergency services. Global coordination is for a universally low-cost vaccine and to support countries with limited health capacity. Large, temporary and targeted support is urgently needed for affected workers and firms until the emergency abates. As the shutdowns end, broad-based, coordinated fiscal stimulus-where financing conditions permit-will become more effective in fostering the recovery. Chapter 2 argues that fiscal policies are at the forefront of facilitating an economic recovery from the COVID-19 pandemic once the Great Lockdown ends. Policymakers can achieve this objective with IDEAS: Invest for the future-in health systems, infrastructure, low carbon technologies, education, and research; adopt well-planned Discretionary policies that can be deployed quickly; and Enhance Automatic Stabilizers, which are built-in budgetary tax and spending measures that automatically stabilize incomes and consumption. Importantly, improving unemployment benefit systems and social safety nets can protect household incomes from adverse shocks and strengthen resilience against future epidemics. Over the past decade, state-owned enterprises (SOEs) have doubled in importance among the world's largest corporations. They often deliver basic services such as water, electricity, and loans for families and small businesses. At their best, they can help promote higher economic growth and achieve development goals. However, many are a burden to taxpayers and the economy. Chapter 3 discusses what governments can do to get the most out of SOEs. This includes ensuring the firm's managers have the right incentives and there is effective oversight. It also requires a high degree of transparency of their activities.